A Review of Optoelectronic Oscillators for High Speed Signal Processing Applications. (29th April 2013) - Devgan, Paul
Abstract : The Optoelectronic Oscillator (OEO) was first demonstrated in 1996 as a low phase noise RF source. Low phase noise RF sources have uses for multiple applications, ranging from analog to digital converters to radar to metrology. In the past sixteen years, the OEO has been shown to be useful for other signal processing applications. This paper will provide a background of the OEO's principles of operation, as well as multiple examples of signal processing applications where the OEO can be used. The OEO can be applied to both analog and digital problems, providing new techniques to solve these challenges.